Water governance for sustainable development: International practices and implications for the Mekong Delta region - Võ, T?t Th?ng (University of Economics Ho Chi Minh City, 2023)
Water governance takes a vital role in sustainable development in the developing world. Population growth, economic development and technological improvement have raised the water demand but water supply is becoming unstable due to natural changes. Water scarcity leads to not only environmental pressures but also social tensions due to the fact that water resources are distributed unevenly across countries, regions, and social groups. In this paper, we firstly review water governance around the world and then investigate the water governance issues in Vietnam, especially in the Mekong Delta. International practices including tools, models and challenges of water governance would be valuable lessons for water policies in Vietnam.